Internalisasi Nilai Amanah Dalam Penyusunan Laporan Keuangan Melalui Pendekatan Al-Qur’an (PKM Di Yayasan Rezky Syafaat) - Resti .; Siti Walida Mustamin; Ukhrima Giastri Putri Muktamar; Ramadani Salam; Fadiyah Nabila Asrijal; Nur Apriliana. S; Rahmah Nikmatullah; Amrah Nurfaiqah; Lutfiah Putri; Aidil Fitrah (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
This community service program aims to internalize the value of trustworthiness in the preparation of school treasurer financial reports through a Qur'anic approach, specifically QS. Al-Baqarah verse 282, which emphasizes the importance of honest and orderly recording of transactions. The activity was carried out at the Rezky Syafaat Foundation, Makassar City, South Sulawesi, with school treasurers as the main target group, as they are responsible for managing the institution's finances. The methods used included initial observation, counseling, and  interactive discussions. The results of the activity showed an increase in school treasurers' understanding of the importance of transparent, accountable financial recording in accordance with Islamic values. The Al-Qur'an approach proved to be effective in building moral awareness and professionalism in school financial management. This program is expected to become a model for the application of trust-based accounting in private education.